Формування підсистеми управління інтелектуальним капіталом у складі системи управління підприємством - Гусаковська, Тетяна Олександрівна; Кужель, Наталія Леонідівна (НТУ "ХПІ", 2015)
Запропоновано рекомендації до формування підсистеми управління інтелектуальним капіталом у складі системи управління підприємством. У складі підсистеми управління інтелектуальним капіталом виділено такі складові, як управління людським капіталом, управління організаційним та управління клієнтським капіталом, управління інформаційним забезпеченням і комунікаціями. Система управління інтелектуальним капіталом виступає в ролі координуючого центру, що має забезпечити узгодженість дій всіх існуючих складових системи управління підприємства, де це стосується формування та використання інтелектуального капіталу.

Recommendations to the formation of intellectual capital management subsystem in the system of enterprise management are proposed, its main tasks and functions are defined. As part of the system of intellectual capital under management tasks and components of intellectual capital allocated to such components as human capital management, organizational management and management of client-side capital, management of datawareand communications. The task of the dedicated system is to ensure the proper execution of specific functions related to the management of intellectual capital. In addition, intellectual capital management system acts as a coordinating center that will ensure coherence of all existing components of the management company, where it concerns the formation and use of intellectual capital. Studies have shown that the use of this management system does not require a significant increase in the number of staff, as compared to the results that it provides, its use is effective.
Forming of the subsystem of intellectual capital management as a part of the enterprise management system
Keywords: інтелектуальна власність; людський капітал; організаційний капітал; капітал відносин; нематеріальні активи; intellectual property; human capital; organizational capital; relationship capital